Humanizing Learning: Implementing the Humanistic Approach in Inclusive Islamic Education at SD Muhammadiyah Wringinanom Gresik - Patty, Muh Akbar; Prastowo, Andi; Sahmat, Sulhu Diah Rafidiah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Abstract: Humanism is one meaningful learning approach that engages students in learning activities. In facing the challenges of inclusive education in Indonesia, implementing Humanistic Learning Theory becomes very relevant and strategic. This research explores the implementation of a humanistic approach in inclusive classrooms at SD Muhammadiyah Wringinanom, Gresik. Using a descriptive qualitative method, data were collected through interviews, classroom observations, and document analysis. The study focused on how humanistic principles, such as respect for individuality, emotional well-being, and social development, are applied in inclusive education. Results highlight the effective use of student-centered learning and the importance of positive teacher-student relationships. However, challenges remain in the lack of specialized teachers for students with disabilities. The study emphasizes the need for more teacher training and resource allocation to improve inclusive education further. Collaboration between teachers, parents, and external organizations is essential for successfully implementing humanistic principles in Islamic educational contexts. Further research is recommended to explore the long-term benefits of the humanistic approach for diverse learners. Abstrak: Humanistik merupakan salah satu pendekatan pembelajaran yang sangat bermakna dengan menjadikan siswa sebagai subjek yang aktif dalam kegiatan pembelajaran. Dalam menghadapi tantangan pendidikan inklusi di Indonesia, implementasi Teori Belajar Humanistik menjadi sangat relevan dan strategis. Penelitian ini mengeksplorasi implementasi pendekatan humanistik di kelas inklusif SD Muhammadiyah Wringinanom, Gresik. Menggunakan metode deskriptif kualitatif, data dikumpulkan melalui wawancara, observasi kelas, dan analisis dokumen. Penelitian ini berfokus pada penerapan prinsip-prinsip humanistik, seperti penghargaan terhadap individualitas, kesejahteraan emosional, dan pengembangan sosial dalam lingkungan pendidikan inklusif. Hasil penelitian menunjukkan penerapan pembelajaran berpusat pada siswa yang efektif dan pentingnya hubungan positif antara guru dan siswa. Namun, tantangan masih ada dalam ketiadaan guru khusus bagi siswa berkebutuhan khusus. Penelitian ini menekankan perlunya pelatihan guru yang lebih intensif dan alokasi sumber daya untuk meningkatkan pendidikan inklusif. Kolaborasi antara guru, orang tua, dan organisasi eksternal sangat penting untuk keberhasilan penerapan prinsip-prinsip humanistik dalam konteks pendidikan Islam. Penelitian lanjutan dianjurkan untuk mengeksplorasi manfaat jangka panjang pendekatan humanistik bagi siswa dengan kebutuhan beragam.